Modifikasi Postural dari Standar Manuver Valsalva untuk Perawatan Kedaruratan pada Takikardia Supraventrikular - Ii Ismail; Diana Irawati; Kuraesin Kuraesin (Journal of Telenursing (JOTING), 2022)
This study aims to determine the effectiveness of the modified valsalva maneuver in restoring sinus rhythm in patients presenting to the emergency department of the Harapan Kita National Heart Hospital Jakarta with Supraventricular Tachycardia (SVT). The method used is quantitative with a pre-experimental research design. The results showed that the modified valsalva maneuver affected systolic and diastolic blood pressure and heart rate, with the average difference between pre and post-valsalva maneuver modification being 0.399 in systole; 0.075 in diastole; and a heart rate of 0.081. In conclusion, the valsalva maneuver modification is able to change the SVT ECG image into a Sinus Rythem ECG. Keywords: Modified Valsalva Maneuver, Emergency Treatment, Supraventricular Tachycardia